2008
DOI: 10.1103/physrevd.78.044032
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mechanics of graphity models

Abstract: Graphity models are characterized by configuration spaces in which states correspond to graphs and Hamiltonians that depend on local properties of graphs such as the degrees of vertices and numbers of short cycles. As statistical systems, graphity models can be studied analytically by estimating their partition functions or numerically by Monte Carlo simulations. Results presented here are based on both of these approaches and give new information about the high-and low-temperature behavior of the models and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…When it comes to quantum phase transitions however, the relative interaction strengths are of the essence. In future work, we would be interested in applying the techniques developed in this paper to Quantum Graphity [18,19], a model of quantum gravity where it is believed that space emerges from spacetime via a quantum phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to quantum phase transitions however, the relative interaction strengths are of the essence. In future work, we would be interested in applying the techniques developed in this paper to Quantum Graphity [18,19], a model of quantum gravity where it is believed that space emerges from spacetime via a quantum phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Other developments of significant interest include [16,17] which show that it is possible to entangle macroscopically separated nanoelectromechanical oscillators of the oscillator chain and that the resulting entanglement is robust to decoherence. Such a system is of great interest for its possible application as a quantum channel and as a tool to investigate the boundary between the classical and quantum worlds.The LRBs have found a more exotic use in the field of emergent gravity, where one wants to study locality, geometry and Lorentz symmetry as emergent phenomena [22,23]. An example of the usefulness of the Lieb-Robinson bounds can be found in [24], where it was shown that in spin systems with emergent electromagnetism [19], the speed of light is also the maximum speed of signals, without imposing from the beginning any Lorentz invariance.…”
mentioning
confidence: 99%
“…The LRBs have found a more exotic use in the field of emergent gravity, where one wants to study locality, geometry and Lorentz symmetry as emergent phenomena [22,23]. An example of the usefulness of the Lieb-Robinson bounds can be found in [24], where it was shown that in spin systems with emergent electromagnetism [19], the speed of light is also the maximum speed of signals, without imposing from the beginning any Lorentz invariance.…”
mentioning
confidence: 99%
“…In this approach, using the average degree of the graph as an order parameter, it was found that as the number of vertices goes to infinity, the critical temperature of the geometrogenic phase transition goes to zero [13]. Another approach has been to estimate the partition function of the model by considering which types of graphs will contribute most [15]. The two main competing families of graphs are homogeneous lattice-like graphs (due to their low energy and consequent high Boltzmann factor) and random graphs (despite being higher in energy, the large number of random graphs means that they contribute significantly).…”
Section: Introductionmentioning
confidence: 99%